2006
DOI: 10.1002/app.23031
|View full text |Cite
|
Sign up to set email alerts
|

Bound rubber in chlorobutyl compounds: Influence of filler type and storage time

Abstract: Bound rubber (BdR) is considered as a measure of the filler-polymer interaction in rubber compounds. The variation of the BdR content with storage time was studied in chlorobutyl compounds filled with fillers like carbon black, carbon-silica dual phase filler (CSDPf), silica, and nanoclays. The effect of the addition of a silane coupling agent on the BdR in carbon black and silica filled compounds was also studied. The BdR content increased with storage time in all compounds. The increase in BdR was higher dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Here we would like to add that it has been a matter of challenge and controversy to give a direct support in favor of the existence of a thin rubber layers on the surface of solid particles as far as the concept of bound rubber and related chain dynamics are concerned. In several literatures the dynamics of such relatively rigid glassy like layers are discussed . Nevertheless, in present case the existence of such rubber chains on the silica surface is directly evidenced through detailed morphological investigation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Here we would like to add that it has been a matter of challenge and controversy to give a direct support in favor of the existence of a thin rubber layers on the surface of solid particles as far as the concept of bound rubber and related chain dynamics are concerned. In several literatures the dynamics of such relatively rigid glassy like layers are discussed . Nevertheless, in present case the existence of such rubber chains on the silica surface is directly evidenced through detailed morphological investigation.…”
Section: Resultsmentioning
confidence: 90%
“…It is a well known fact that the strong rubber–filler interaction leads to the formation of bound rubber content on the surface of filler which may take place via physorption, chemisorption or mechanical interaction . A bound rubber model was suggested in several reports where tightly and loosely bound rubber, surrounding the filler particles, had been shown to act as an additional crosslink in the rubber matrix . In this study, an effort has been paid to visualise the bound rubber on the surface of the silica particles by detailed morphological investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The BdR content can be considered as a measure of polymer–filler interactions, which mainly depends upon the surface area and the surface activity of fillers. 20 MWCNT has very high surface that leads to higher level of interactions with polymer matrix. The BdR content of MWCNT-filled rubber is increased with increase in filler loading, which is clearly observed from Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample is weighed by a sensitive balance. The testpieces were immersed in solvents, for different periods of time (15,30, 45 and 60 min), wiped thoroughly and reweighed. It was found that the equilibrium degree of swelling was attained after an immersion time of 24 h. The degree of swelling was calculated according the relation…”
Section: Swelling Studiesmentioning
confidence: 99%